The Effect of TRX Suspension Resistance Exercises on Certain Physical Variables and the Accuracy of Performing the Offensive Block Skill in Volleyball - Ibrahim , Shaimaa; Hassan , Dania (Journal of Physical Education, 2025)
The study aimed to develop resistance suspension (TRX) exercises to improve certain physical variables and the accuracy of performing the offensive block skill in volleyball. The experimental method was employed on a sample of 20 players from Al-Hussein Sports Club for Volleyball, who were intentionally selected. The sample’s mean height was 171.25 cm with a standard deviation of 5.5 cm, the mean weight was 61.23 kg with a standard deviation of 4.656 kg, and the mean age was 16.88 years with a standard deviation of 0.52 years. Pre-tests were conducted on the sample before implementing the training program, which lasted for eight weeks at a frequency of three training sessions per week. After the program, post-tests were conducted, and data from physical and skill performance tests were collected and analyzed using the SPSS statistical program. The results showed statistically significant differences in all studied variables (arm strength endurance, leg strength endurance, physical-skill performance endurance, and blocking accuracy), with (Sig) values of (0.000, 0.005, 0.000, and 0.000) respectively. The researchers concluded that TRX suspension resistance exercises had a positive impact on the development of physical variables for volleyball players. These exercises also improved the accuracy of performing the offensive block skill, which was attributed to the physical development of the sample, leading to improved performance and better match outcomes. The researchers recommended conducting similar studies on other samples and incorporating TRX exercises in training units due to their effectiveness in developing physical qualities and enhancing the accuracy of the offensive block skill.